Historical patterns of economic growth in Africa: a review - Morten Jerven (African Economic History Network (AEHN), 2016)
The study of long term growth in Africa has recently been invigorated by the work of economists. To date, this literature has been motivated by explaining a divergence of income and has focussed on finding persistent factors that can explain a chronic failure of growth in Africa. This chapter reviews some periods of economic growth in the past two centuries, and suggest that there must be more to learn from studying these periods of economic change and accumulation, particularly because they were accompanied by significant changes in institutions, or how the economy and the society was organized. The African economic history literature does emphasise dynamism - as opposed to persistence, and diversity in outcomes across time and space - in contrast to the average stagnation that has prompted the economic literature. In sum, there is more to learn from studying the history of economic growth in the African past, than what can be gauged from a search for a root cause of African economic underdevelopment.
Keywords: E01; N00; N17; N57; N67; 330; Economic History; Economic Development; Economic Growth; Development Economics; External Trade